What Are The Most Effective Management Strategies For Psoriasis During Pregnancy That Minimize Risks To Maternal And Fetal Health? : A Systematic Review - Ni Putu Devi Gema Partamayani; Anak Agung Istri Indah Paramita; Natasha Caroline Gigir (The International Journal of Medical Science and Health Research, 2025)
Introduction: Psoriasis, a chronic inflammatory skin disease, affects 2–3% of the global population, including women of childbearing age. Managing psoriasis during pregnancy presents a challenge, balancing maternal disease control with fetal safety, as physiological changes can influence disease severity. Individualized treatment plans are necessary, prioritizing medications with established safety profiles to minimize risks to both mother and fetus while ensuring effective disease control. Methods: This systematic review adhered to the PRISMA 2020 guidelines to ensure methodological rigor and accuracy. Data extraction was performed using a large language model, focusing on study design, population characteristics, management strategies, maternal and fetal health outcomes, and risk of bias. The search strategy employed Boolean MeSH keywords across databases like PubMed, Semantic Scholar, Sagepub, and Google Scholar. Results: Forty studies were included in the systematic review. Biologic therapies, such as TNF inhibitors and ustekinumab, showed acceptable safety profiles with miscarriage rates (8.9–15.3%) and congenital malformation rates (3–4%) comparable to the general population. Certolizumab pegol notably exhibited minimal placental transfer. Methotrexate is contraindicated due to teratogenic effects. Sulfasalazine demonstrated modest efficacy with few serious adverse events. Topical treatments generally lacked robust pregnancy-specific safety data. Discussion: Biologic therapies are effective and generally safe for psoriasis management during pregnancy, with certolizumab pegol being a preferred choice due to minimal placental transfer. Discontinuation of biologics may lead to disease flares, necessitating individualized risk-benefit assessments. Preconception counseling, close monitoring, and shared decision-making are crucial for optimizing outcomes. Conclusion: Effective management of psoriasis during pregnancy balances maternal disease control with fetal health. Biologics offer acceptable safety profiles, with certolizumab pegol being particularly favorable. Methotrexate is contraindicated, and topical treatments require more research for definitive safety recommendations. A multidisciplinary and patient-centered approach, including preconception counseling and close monitoring, is essential to optimize care.